REAL ESTATE AND ITS FEATURES - Mamadjanova Odina Alisher kizi; Botrova Yulduz Rojzibaevna (Journals Park Publishing, 2022)
In this article, opinions are expressed on real estate and its types, the decisions taken by our state on property of individuals and legal entities and cases of execution of laws.
Keywords: law; decision; property